Implementasi Penegakan Hukum Tindak Pidana Ringan (Suatu Diskursus Tindak Pidana Miras Di Polres Jombang) - Muhammad Naufal Arifiyanto; Eko Januar Pribadi (Faculty of Law Hang Tuah University, 2018)
This study aims to (1) understand, identify and analyze the criminal acts of the law enforcement process liquor in the year 2014 to 2015 in Jombang Police. (2) to understand, identify and analyze the implementation of the law of criminal offenses liquor. (3) to understand, identify and analyze causal criminal offense liquor. This type of research is descriptive research with a qualitative approach seeks to describe or provide an overview of the phenomenon and the events that occurred. The location of this research at the police station and Jombang Jombang.Data collection techniques in this research is observation, interview, and documentation. This data is analyzed by using the method of collection, reduction and verification and presented in the form of descriptive analysis. The conclusion in this study (1) The Regional Regulation No. 16 of 2009 on the supervision and control of liquor in Jombang has been efficient and effective as existing laws regulate the circulation of liquor. (2) Local legislation is able to address the problemsarising from the crime of drinking. With sanctions that still apply 10% (ten percent) of the maximum sanction, it is expected to be free liquor can be added as a reference Jombang zero in offenses liquor.